Dynamics of HCV epidemiology in Aydin province of Turkey and the associated factors. Issue 2 (21st December 2017) - Kirdar, Sevin; Aydin, Neriman; Tiryaki, Yasin; Ertugrul, Bulent; Coskun, Adil; Bilgen, Mehmet
Abstract : This paper gives an update on the local distributions of HCV genotypes in Aydin province of Turkey, provides a comparison with the previous records, and discusses the potential causal reasons shaping the evolving genotype profiles. Patient files from 2011 to 2016 were retrospectively analyzed, and newly detected cases were documented. Out of 286 patients, male and female ratios were determined to remain nearly the same (~50%). Genotype 1 was still the most common (90.2%), followed by genotype 3 (5.9%), genotype 2 (2.1%), and genotype 4 (1.4%) in frequency. There were international patients (4.50%). One patient had genotyped 2+3 together. Genotypes 4 and 2+3 were detected for the first time, and the patients with genotype 4 were interestingly all male and also domestic individuals. However, these patients traveled or lived abroad in the past due to occupational reasons, thereby likely acquired the infection while abroad. HCV surveillance system is currently inadequate and some infected patients may go undetected in the province. Remapping the regional distribution of HCV genotypes from time‐to‐time is required for identifying the local dynamics and causes leading to it. This process enhances the clinical preparation and readiness for the better management of the disease.